Changes in Pramipexole Utilization after Introduction of the Extended-Release Formulation: A Nationwide Study in Taiwan - K. Arnold Chan; Yu-Chun Hsieh; Shu-Feng Hsieh; Rou-Shayn Chen (Adis, Springer Healthcare, 2020)
Abstract Background Real-world impact of extended-release formulations of oral drugs should ideally be evaluated in population-based health data. Objective To evaluate changes in utilization of the dopamine agonist pramipexole for Parkinson's disease after the introduction of extended-release (ER) pramipexole in Taiwan. Patients and Methods Source data were derived from National Health Insurance claims. Patients with a diagnosis of Parkinson's disease and pramipexole prescriptions were identified. Drug use patterns from 2009 through 2011 (only the immediate-release [IR] formulation was available) and from 2012 through 2017 (both the IR and ER formulations were available) were assessed. Outcomes of interest were levodopa equivalent dose per day (LEDD) and 1-year adherence, as measured by the medication possession ratio (MPR). Results LEDDs associated with pramipexole ER prescriptions were more than twice as large as that associated with pramipexole IR, both in pramipexole used in monotherapy and that used in combination therapy. One-year MPRs for pramipexole ER initiators were all larger than 73% from 2012 through 2016 and 1-year MPRs for pramipexole IR initiators were less than 65% in 2010 and 2011. Conclusion Introduction of pramipexole ER to Taiwan resulted in higher LEDD in prescriptions with pramipexole. Patients with Parkinson's disease who were initiated on pramipexole ER had better adherence to the medication than those who were prescribed pramipexole IR.